Agglomeration Economies in Classical Music - Karol J. Borowiecki (European Historical Economics Society (EHES), 2013)
This study investigates agglomeration effects for classical music production in a wide range of cities for a global sample of composers born between 1750 and 1899. Theory suggests a trade-off between agglomeration economies (peer effects) and diseconomies (peer crowding). I test this hypothesis using historical data on composers and employ a unique instrumental variable – a measure of birth centrality, calculated as the average distance between a composer's birthplace and the birthplace of his peers. I find a strong causal impact of peer group size on the number of important compositions written in a given year. Consistent with theory, the productivity gain eventually decreases and is characterized by an inverted U-shaped relationship. These results are robust to a large series of tests, including checks for quality of peers, city characteristics, various measures of composers' productivity, and across different estimations in which also time-varying birth centrality measures are used as instrumental variables.
Keywords: D24; J24; N90; R12; Z11; 330; agglomeration economies; density effects; peer effects; productivity; urban history; cities; composer